PLAGIARSM: MENGAPA HARUS TERJADI? - FX Supriyono (Bina Ekonomi, 2010)
The purpose of this article is to describe a hot issue called plagiarism. Even though, this is not a simple matter and even some people said that it is a mission impossible, higher education should participate to overcome the problem. The problems of plagiarism exist 'because of many reasons. First it is caused by internal factors, such as personality; values and low appreciation of science. Second it is merely 'caused by external factors such as education system, promotion system, character building, reading habits and control of the institution.  Therefore, several  steps should be taken, such as emphasizing  of the character building  in the process  of learning; providing  the system  control and improving  the process  of consultation. By doing this steps, it is possible to minimize that deviant behavior.